A New Pressure Guided Management Tool for Epidural Space Detection: Feasibility Assessment on a Simulator. Issue 12 (25th October 2017) - Carassiti, Massimiliano; Mattei, Alessia; Quarta, Rossella; Massaroni, Carlo; Saccomandi, Paola; Tesei, Marco; Setola, Roberto; Schena, Emiliano
Abstract: The detection of epidural space is usually performed by the technique of loss of resistance (LOR) without technological support, although there are few commercial options. We sought to design and develop a new noninvasive system able to detect the LOR without any changes to the conventional procedure. It allows detecting the LOR by a custom made algorithm. The system provides a visual and acoustic feedback when the LOR is detected. We optimized the detection algorithm and investigated the performance of the system during experiments on a custom simulator. During the experiments performed by 10 anesthetists and 10 trainees, the pressure exerted on the syringe plunger was monitored using the custom‐made system. Each participant performed four experiments using the system on the simulator. The performance of the system in LOR detection was evaluated comparing the feedback activation and the breaches of the last layer of the simulator. Moreover, each participant filled out a questionnaire to assess how the procedure with the simulator mimics the clinical scenario. A higher questionnaire score corresponds to a more realistic condition (0 = not real, 5 = extremely real). Results showed that the LOR was detected in 74 of the 80 trials (92.5% of the cases); the anesthetists obtained better results than trainees: 97.5 versus 87.5%. The questionnaires showed that all the participants found the trial realistic (score ≥3); anesthetists found it more realistic than trainees (4.2 ± 0.78 vs. 3.8 ± 0.78, mean ± SD). In summary, the proposed system successfully detected the LOR in the large part of the trials. The participants found the trials realistic. A higher success rate was observed in the anesthetists group.